Efektifitas Mobilisasi Scapula terhadap Penurunan Nyeri Shoulder pada Kasus Subacromial Impingement Syndrome di RS. Marsudi Waluyo Malang - Ida Bagus Made Dharma Putra; Agung Hadi Endaryanto; Dian Pitaloka Priasmoro; Ahmad Abdullah (FORIKES, 2021)
Subacromial impingement is a condition of pain and limitation in the shoulder caused by narrowing of the subacromial space. One of the physiotherapy treatments is scapula mobilization which is intended to overcome shoulder pain by mobilizing the scapula with a slide movement in four directions of the scapulothoracic joint which aims to release tissue adhesions and relax the muscles around the shoulder. This study aims to determine the effectiveness of scapula mobilization in cases of subacromial impingement syndrome. This type of quasiexperimental research uses a one test group design conducted in August – October 2021 at the Medical Rehabilitation Installation of Marsudi Waluyo Hospital Malang, with 30 people used a purposive sampling technique with 15 samples and a Visual Analogue Scale (VAS) measuring instrument. The frequency of therapy is 8 times, giving scapula mobilization, a dose of 2 sets per 1 set of 10 repetitions with a 30 second rest between sets. The data was processed through paired sample t-test with the results of the mean pre 6.0267 and post 3.833 with a difference of 0.601; 95% CI between 1.7481 – 2.638 obtained a p value of 0.000 (<0.05). With the conclusion that, scapula mobilization is effective in reducing subacromial impingement syndrome pain.Keywords: subacromial impingement syndrome; pain; scapula mobilizationABSTRAKSubacromial impingement merupakan kondisi nyeri dan keterbatasan pada bahu yang diakibatkan karena penyempitan ruang subacromial. Salah satu penanganan Fisioterapi adalah mobilisasi scapula yang ditujukan untuk mengatasi nyeri bahu dengan memobilisasi scapula dengan gerakan slide ke empat arah sendi scapulothoracic yang bertujuan untuk melepaskan perlengketan jaringan dan rileksasi otot sekitar bahu. Penelitian ini bertujuan untuk mengetahui efektivitas mobilisasi scapula pada kasus subacromial impingement syndrome. Jenis penelitian quasi experiment menggunakan one test group design yang dilakukan pada bulan Agustus – Oktober 2021 di Instalasi Rehabilitasi Medik RS Marsudi Waluyo Malang, dengan 30 orang populasi menggunakan teknik purposive sampling dengan 15 sampel dan alat ukur Visual Analogue Scale (VAS). Frekuensi 8 kali terapi pemberian mobilisasi scapula, dosis 2 set tiap 1 set 10 kali repetisi dengan jeda 30 detik fase istirahat antar set. Data diolah melalui paired sample t-test dengan hasil nilai mean pre 6,0267 dan post 3,833 selisih 0,601; IK95% antara 1,7481 – 2,638 memperoleh nilai p 0,000 (<0,05). Dengan kesimpulan bahwa, mobilisasi scapula efektif menurunkan nyeri subacromial impingement syndrome.Kata kunci: subacromial impingement syndrome; nyeri; mobilisasi scapula